2017
DOI: 10.1248/bpb.b16-00899
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Administration of Aucubin Inhibits Paclitaxel-Induced Mechanical Allodynia <i>via</i> the Inhibition of Endoplasmic Reticulum Stress in Peripheral Schwann Cells

Abstract: Paclitaxel is a chemotherapeutic agent that causes peripheral neuropathy as its major dose-limiting side effect. However, the peripheral neuropathy is difficult to manage. A study we recently conducted showed that repetitive administration of aucubin as a prophylactic inhibits paclitaxel-induced mechanical allodynia. However, the mechanisms underlying the anti-allodynic activity of aucubin, which is a major component of Plantaginis Semen, was unclear. In addition to mechanical allodynia, aucubin inhibited spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…184 Another study found that a single intraperitoneal injection of Ptx (5 mg/kg) was sufficient to induce CHOP expression in the sciatic nerve, increase the excitability of spinal dorsal horn neurons, and lead to mechanical allodynia in C57BL/6 NCr mice. 40,185 In vitro, Ptx treatment of SK-N-SH neuroblastoma cells increased the phosphorylation of eIF2a and induced the expression of CHOP as well as the pro-apoptotic caspase 3 186,187 Furthermore, pretreatment with fluvoxamine, a Sigma 1 receptor inducer, and BiP-inducer X (BIX) attenuated ER stress and protected the SK-N-SH cells from paclitaxel-associated cytotoxicity. 187 However, whether these drugs can mitigate pain in CIPN remains to be investigated.…”
Section: Er Stress In Chemotherapy-induced Peripheral Neuropathymentioning
confidence: 99%
“…184 Another study found that a single intraperitoneal injection of Ptx (5 mg/kg) was sufficient to induce CHOP expression in the sciatic nerve, increase the excitability of spinal dorsal horn neurons, and lead to mechanical allodynia in C57BL/6 NCr mice. 40,185 In vitro, Ptx treatment of SK-N-SH neuroblastoma cells increased the phosphorylation of eIF2a and induced the expression of CHOP as well as the pro-apoptotic caspase 3 186,187 Furthermore, pretreatment with fluvoxamine, a Sigma 1 receptor inducer, and BiP-inducer X (BIX) attenuated ER stress and protected the SK-N-SH cells from paclitaxel-associated cytotoxicity. 187 However, whether these drugs can mitigate pain in CIPN remains to be investigated.…”
Section: Er Stress In Chemotherapy-induced Peripheral Neuropathymentioning
confidence: 99%
“…Taken together, it is suggested that the alteration of plasma level of aucubin and inhibition of PTX-induced allodynia do not have direct correlation. Antiallodynic activity by repetitive administration of aucubin may be due to organic protection, such as the protection of demyelination [23].…”
Section: Discussionmentioning
confidence: 99%
“…We reported that intraperitoneal injection of 1 inhibited firing induced by mechanical stimuli in spinal dorsal horn neurons in PTX-treated mice. Furthermore, an endoplasmic reticulum (ER) stress inhibition mechanism is suggested by the inhibitory effect of 1 on the PTX-induced expression of CCAAT/enhancer-binding protein homologous protein, a protein marker of ER stress, in the mouse sciatic nerve and LY-PPB6 cells (a rat Schwann cell line) [23]. Demyelination associated with chronic pain is induced by PTX in peripheral nerves [25,26], because PTX causes damage in the Schwann cells [25], which form myelin sheaths, via ER stress [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The results from experimental studies are still not consistent because the activation of microglial cells has been observed in another study [103]. In a study by Imai et al, it was shown that cisplatin and oxaliplatin may induce mitochondrial dysfunction in cultured Schwann cells, followed by numerous disturbances in molecular function and cellular structure contributing to peripheral neuropathy [64,104].…”
Section: Platinum-based Antineoplastics (Oxaliplatin Cisplatin Anmentioning
confidence: 99%